Development of a charging system for electric vehicles in Singapore - Lim, Thomas Hiap Teck (2014)
This paper discusses on the implementation of using solar as one of the natural energy to develop a charging system for electric vehicle. Due to the rising cost of fossil fuels, users have been looking into option of electric vehicle as their alternative mean of transport.